2020
DOI: 10.1101/2020.06.19.162420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the Siemens Trio to Prisma Upgrade and Volumetric Navigators on MRI Indices: A Reliability Study with Implications for Longitudinal Study Designs

Abstract: Many magnetic resonance imaging (MRI) indices are being studied longitudinally to explore topics such as biomarker detection and clinical staging. A pertinent concern to longitudinal work is MRI scanner upgrades. When upgrades occur during the course of a longitudinal MRI neuroimaging investigation, there may be an impact on the compatibility of pre-and postupgrade measures. Similarly, subject motion is another issue that may be detrimental to longitudinal MRI work; however, embedding volumetric navigators (vN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
1
7
2
Order By: Relevance
“…The results of our study are in line with previous findings which have indicated systematic effects of scanner upgrade on GM imaging outcomes (Lee et al 2019;Han et al 2006;Jovicich et al 2009;Brunton et al 2015). Notably, in two recent studies, an upgrade from Magnetom Trio to Prismafit induced a significant increase in cortical thickness (CT) and volume as well as differences in subcortical volumes (Potvin et al 2019;Plitman et al 2020). Similar to our findings, ICC values for cortical measures were good to excellent in both studies.…”
Section: Comparison To Previous Upgrade Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…The results of our study are in line with previous findings which have indicated systematic effects of scanner upgrade on GM imaging outcomes (Lee et al 2019;Han et al 2006;Jovicich et al 2009;Brunton et al 2015). Notably, in two recent studies, an upgrade from Magnetom Trio to Prismafit induced a significant increase in cortical thickness (CT) and volume as well as differences in subcortical volumes (Potvin et al 2019;Plitman et al 2020). Similar to our findings, ICC values for cortical measures were good to excellent in both studies.…”
Section: Comparison To Previous Upgrade Studiessupporting
confidence: 92%
“…CNR and other measures of image quality indicated higher quality on the (earlier) Verio scanner. In contrast, studies investigating the effects of real upgrades showed increased image quality (quantified as signal-to-noise ratio (SNR) or CNR) after the upgrade (Potvin et al 2019;Plitman et al 2020). This may contribute to the observed bias pattern in GMV, yet increased SNR/CNR was also associated with higher CT in our study, independent of scanner-dependent regional CT differences (Shuter et al 2008;Potvin et al 2019).…”
Section: Comparison To Previous Upgrade Studiescontrasting
confidence: 87%
See 2 more Smart Citations
“…Similarly, sequence-related differences in subcortical structures have recently been found using CAT-12 (personal communication with J.-L. Martinot). Further, a scanner update was completed during wave three in Paris (Siemens Trio to Prisma) which may have introduced additional bias in results as Medawar et al (2020) and Plitman et al (2020) reported very good ICC but also percent volume differences in several cortical and subcortical regions when comparing Siemens Scanners (Trio versus Prisma / Verio versus Skyra). Since many recent longitudinal studies on brain development included several samples with differences in imaging sequence and scanner type (Dennison et al, 2013; Mills et al, 2021; Tamnes et al, 2017; Wierenga, Sexton, et al, 2018), results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%